BAIT AL-ḤIKMAH DAN KONTRIBUSINYA DALAM PERKEMBANGAN TRADISI KEILMUAN ISLAM PADA ERA ABBASIYAH - Salahuddin Salahuddin (State Institute of Islamic Studies (IAIN) Palu, 2011)
Abstract: The Period of Abbasid rule was also called the golden age of Islam. It was so called since in that period, some Muslim scholars in the field of Islamic law and philosophy emerged. The emergence of Muslim scholars at that time was closely related to the obligation to search knowledge in Islam and the supports of the caliphs. It is because of the obligation that a translation institution called Bait al-Ḥikmah was established. In this institution, the Greek works were translated into Arabic. The translation works were then completed with new thoughts of the translators and spread out to Syria, Spain and Cecilia. It was the dominant basis for the development of science in the West since the beginning of the Renaissance era. Kata Kunci: Bait al-Ḥikmah, tradisi keilmuan Islam, era Abbasiyah